Plant pathology - George N Agrios (Academic Press, 1997)
The book includes discoveries and improvements in molecular plant pathology, biological control, computers, and taxanomy of mocroorganisms, and the emergence of new plant pathogenetic microorganisms. Most improvements have been in the area of molecular genetics of plant disease resistance to pathogens